Predictability of Sex from Frontal Sinus in Nepalese Population - Singh, P. K.; Paudel, R. C.; Menezes, R. G. (Kathmandu University Medical Journal, 2021)
Background Various methods had been used for personal identification. Scientific basis of identification was initiated and progressed after 19th century which may be attributed to various scientists. With the invention of X-ray the field of identification further progressed. Modern radiological diagnostic equipments have greatly assisted in the field of forensic. Frontal sinuses are paired lobulated air cavities located posterior to superciliary arches in the frontal bone. Computed Tomography is best used to study frontal sinuses. Objective To evaluate bilateral Frontal sinus for sexual dimorphism using Computed Tomography. Method Anterior posterior length, transverse width and height of the bilateral Frontal sinus were directly measured on CT DICOM image, using Electronic Caliper in DICOM viewer software. A total 100 CT scans, 50 of each sex were collected was analysed using SPSS-20 in present study. Result The mean age distribution for male is 34.74±8.66, and for females 35.34±8.88. The mean of all the measurements take was larger in males in comparison to females with p < 0.00. The paired t test showed left side is larger than right. The discriminant function showed high significance for each measurement and also when all the measurements were combined. Conclusion Though the study being unique for Nepalese population, caution should be taken when frontal sinus is used as the only parameter. However in combination with other morphometric data is advised.